RELEVANSI KURIKULUM FAKULTAS PSIKOLOGI UIN SUNAN GUNUNG DJATI BANDUNG DENGAN DUNIA KERJA - Mursidin mursidin; Ulfiah Ulfiah; Ening Ningsih (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2008)
Curriculum is one of the important components in education which has a big role in determining the direction and purpose that will be reached by the academic institution. Therefore, curriculum must be designed on the basis of curriculum development principles should be noticed. One of the principles is the curriculum relevance with the employment. So, to evaluate the curriculum, including psychology faculty UIN SGD Bandung, it can be conducted by scrutinizing how far the curriculum relevance with occupation.To scrutinize how far the curriculum relevance with occupation, we can trace from alumni’s feed back. So, in this research it has been scrutinized how curriculum relevance of psychology faculty UIN SGD Bandung with the occupation taken from alumni’s view, the job appropriateness with the competence and psychology profession, and the hope of alumni to curriculum change.The data of research are processed either qualitative approach or quantitative by descriptive statistic analyzing present age calculation, and level category and also the analysis of contingency coefficient correlation test. From the result of data processing, it shows that most of alumni view that the curriculum of psychology faculty UIN SGD Bandung is still relevant with occupation. It is strengthened by the data showing the most of alumni’s job which generally is still appropriate with the psychology profession scope. It is so with being relatively fast for the alumni to get the job after graduating. It indicates that the products (graduations) of psychology faculty UIN SGD Bandung still have any competition and they are needed by the user.From correlation test result, it can be concluded that there is no respondent’s characteristic which has significant relation with their view to the curriculum relevance of psychology faculty UIN SGD Bandung with occupation. In other word, respondent’s characteristic can’t be a significant correlation to human’s view in curriculum.Although Alumni view curriculum still relevant with occupation, but all respondents still hope any change in curriculum to be more applicative and relevant with human’s need especially for occupation.